HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN PENATALAKSANAAN AWAL DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS PERUMNAS II PONTIANAK TAHUN 2013 - ., Erisa Herwindasari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background- Diarrhea is the major cause of mortality in toddler inIndonesia. The mortality is caused by inappropriate diarrhea managementat home and in health public service. Management of diarrhea at home isaffected by mothers knowledge level. Mothers knowledge level affectedby mothers age, education of mother and occupation of mother.Objective- The aim of this study is to measure the mothers knowledgelevel with early management of diarrhea in toddler.Method- The study was an analytical cross sectional. Data was gainedfrom questionnaire filled by mother who fit inclusion criteria in Posyandu atPuskesmas Perumnas II Pontianak in 2013.Result- There are 73 respondents taken as samples. Thirty seven percentare in good level of knowledge and 63% are in lack level of knowledge.Seventy two point six percent of mother had a good early management ofdiarrhea and 27,4% mother had a bad early management of diarrhea.Data was analyzed with chi- square test showing a significant associationbetween mothers level of knowledge with early management of diarrheain toddler (p= 0,017). Data resulted from multivariate study with logisticregression showing a significant association between mothers age withearly management of diarrhea (OR= 4,019)Conclusion- Early management of diarrhea in toddler is more affected bymothers age than mothers knowledge level. Keyword: diarrhea, mothers level of knowledge, early management